Tunability of magnetization and bandgap in mullite-type Bi2Fe4O9 ceramics through non-magnetic ions. (15th March 2018) - Yuan, Xueyou; Shi, Lei; Zhao, Jiyin; Zhou, Shiming; Guo, Jianhui
Abstract: Polycrystalline Bi2 Fe4 O9 and Bi2 Fe3.6 Me0.4 O9 (Me = Al and Ti) ceramics were prepared using a modified Pechini method. It is observed that the introduction of Ti apparently increases low-temperature magnetization of Bi2 Fe4 O9, while the Al substitution has weakly effect. Meanwhile, the optical bandgap reduces from 2.06 eV for Bi2 Fe4 O9 to1.86 eV for Ti substitution, and 2.01 eV for Al substitution, respectively. All results may be ascribed to the random replacement of both octahedral and tetrahedral Fe ions for Al substitution while preferly replacement of octahedral sites for Ti substitution, as confirmed by the Rietveld refinement and Raman spectra. Graphical abstract: Image 1